2017
DOI: 10.1080/09571736.2017.1298149
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perspective on the benefits of EFL literature education

Abstract: Understanding students' perspectives on the foreign language (FL) curriculum could be considered as a vital step in curriculum design and lesson planning. This study drew on data provided by a single open question survey to investigate the perspective of Dutch secondary school students (N = 635) from 15 different schools with regard to the benefits of literature education in English as a foreign language (EFL). This study also sought to find out whether there are any differences in these perspectives between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 23 publications
6
71
1
Order By: Relevance
“…The current study is part of a larger research project exploring the teaching of literature in EFL classrooms in secondary schools in the Netherlands, where literature is part of the common core curriculum (for an overview see Bloemert, Jansen, & van de Grift, 2016;Bloemert et al, 2019). The larger project responds to the movement, within the global context of foreign language education, towards a re-integration of the domains of language and literature teaching (Carter, 2015).…”
Section: The Present Study: Context Purpose and Research Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study is part of a larger research project exploring the teaching of literature in EFL classrooms in secondary schools in the Netherlands, where literature is part of the common core curriculum (for an overview see Bloemert, Jansen, & van de Grift, 2016;Bloemert et al, 2019). The larger project responds to the movement, within the global context of foreign language education, towards a re-integration of the domains of language and literature teaching (Carter, 2015).…”
Section: The Present Study: Context Purpose and Research Questionmentioning
confidence: 99%
“…Although these frameworks may be practical and valuable, we have previously claimed that most of them lack a theoretical foundation (Bloemert et al, 2016). Through investigating EFL classrooms in a secondary school setting and building on previous theoretical understandings we have proposed a Comprehensive Approach to foreign language-literature teaching and learning model (hereafter: Comprehensive Approach) (Bloemert et al, 2016(Bloemert et al, , 2019. The term 'approach' refers to the focus of the EFL lesson where literature is used.…”
Section: The Present Study: Context Purpose and Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of research designs based on a Likert scale questionnaire, more recent empirical studies such as those by Duncan and Paran (2017) and Bloemert, Paran, Jansen and van de Grift (2019) have surveyed students' perceptions by means of general, open questions about what students think the benefits of EFL literature lessons are (Bloemert et al, 2019). This design was used for the purpose of not inadvertently influencing students' answers.…”
Section: The Use Of Literature In Efl: State Of the Art And Main Chalmentioning
confidence: 99%
“…In Duncan and Paran (2017) this led participants to mainly acknowledge literature's potential to elicit linguistic competence, while cultural and motivational benefits were brought about to a much lesser extent. Following a similar procedure, Bloemert et al (2019), in contrast, reported a much wider spectrum of advantages which they classified into four main approaches: the language approach (linguistic competence), the text approach (knowledge of the typical stylistic features of literature), the reader approach (personal growth), and the context approach (socio-historical knowledge of the period in which the literary text was written). Even though we agree that surveying non-mediated views can provide valuable insights into students' beliefs, we also consider that asking students to react to specific issues or ideas might also be useful for our specific goals, namely to support or refute available theoretical positions on the use of poetry in EFL.…”
Section: The Use Of Literature In Efl: State Of the Art And Main Chalmentioning
confidence: 99%